Effects of plant oligosaccharides derived from dragon fruit on gut microbiota in proximal and distal colon of mice - Saranya Peerakietkhajorn,; Nilobon Jeanmard,; Papatsorn Chuenpanitkit,; Sakena K-da,; Kanrawee Bannob,; Pissared Khuituan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Prebiotic oligosaccharides are used as supplements to improve colon health. Oligosaccharides derived from dragon fruit (DFO) are a mixture of fructo-oligosaccharides (FOS), and have prebiotic properties that increase beneficial bacteria in vitro. This study aimed to investigate changes in gut microbiota in the colon of mice fed a diet supplemented with DFO. Treatment groups were fed 100, 500, and 1000 mg/kg of DFO, 1000 mg/kg FOS and distilled water. The results showed that DFO did not change the body weight of mice, but altered microbiota in the proximal and distal colon. Populations of Blautia, Parabacteroides, and Bacteroides were among the highest proportions of bacteria represented after all treatments. Lactobacillus was also found in the proximal and distal colon. Moreover, qPCR results showed that Bifidobacteria increased in the distal colon of mice treated with 100 and 1000 mg/kg DFO for 14 days, while Lactobacilli increased in the proximal colon of mice treated with 500 mg/kg DFO for 7 days. In contrast, Enterococci decreased in the proximal colon of mice that were given 100, 500, and 1000 mg/kg of DFO and 1000 mg/kg of FOS for 14 days. These results suggested that DFO is capable of increasing populations of beneficial bacteria while decreasing populations of some other bacteria.